Sinergi Organisasi Masyarakat dan Pemerintah Sebagai Aktor Dalam Hukum Lingkungan Di Indonesia - Anisa Hermawati; Sarman Sarman; Harinanto Sugiono (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
The synergy between civil society organizations and the government as actors in environmental law is crucial for the enforcement and protection of environmental law in Indonesia. In the context of increasing environmental issues, active public participation becomes a vital element in monitoring, reporting violations, and advocating for environmental policies. This study aims to analyze the role and forms of synergy between civil society organizations and the government in efforts to protect and manage the environment in Indonesia. The research method employed is normative juridical, which involves legal research conducted through the study of literature or secondary sources. In this library research method, the author uses secondary data obtained from legal literature. The approach used is the statutory approach. This study examines the roles of each actor, the cooperation mechanisms established, and the challenges faced in their implementation